Failure detection algorithm for High-Temperature Superconductor (HTS) breaker arc model - Ullah, A.; Lie, T. T.; Gunawardane, K.; Nair, N. K. C. (Innovative Smart Grid Technologies, 2018)
A failure detection algorithm for High-Temperature Superconductor Circuit breaker (HTSCB) operation is described in this paper in order to detect the faulty operation. The simulation of HTSCB is achieved using an HTS arc models. The arc models is used to define the transient behavior of HTSCB after each operation. The transient signals resulting from electric arc comprise numerous harmonics. Firstly, arc model parameters are defined from parameter sweeping. Then, the Total Harmonic Distortion (THD) index is regarded in diagnosing the circuit breaker (CB) operating mechanism. The simulation of arc model and corresponding signal analyses are performed in MATLAB ® environment. The calculating method is established on the investigation of fast switching timing and characteristics of the HTS breaker arc model.